Danon Cardiomyopathy: Asymmetric Hypertrophy and Extensive Scarring in an Explanted Heart. Issue 3 (May 2021) - Jacobs, Jonathan; Burke, Allen; Drachenberg, Cinthia
Abstract: We report the gross and histologic findings of an explant with Danon cardiomyopathy, and discuss the differential diagnosis of left ventricular hypertrophy with a genetic basis.